The basic algorithm for the design and construction of a monocultural innovation organization - Polyakov, Yuri; Savchenko, Andrey; Alekseeva, Natalia; Panteleeva, Elena; Savelyev, Mikhail (SHS web of conferences, 2020)
Algorithmization of management activities in the transition to the digital economy is one of the most important tasks of modern management science. Sketch design is defined by the algorithm creation tool. This algorithmization method is applied to the processes of choosing the type of a homogeneous product, its quality and other consumer properties, utility for the consumer and manufacturer. Products are classified according to their purpose and the resources for their production. The quality of the product is defined as the ratio of the actual properties of the product to the normative ones, while it is necessary to take into account the influence of manufacturing defects, which entails a transition from linear to non-linear quality functions. The cumulative assessment of the product for the consumer is determined taking into account his subjective assessment of the properties of the product, expressed in the weight of the quality of individual utilities. For a manufacturer, the aggregate assessment of product quality directly depends on the main properties of the product, taking into account its other properties, and inversely depends on the cost of purchasing it, taking into account their functional elasticity. The algorithm is recommended for use by specialists dealing with algorithmic management activities.